A Descriptive Study On Millennial Students’ Preferred Learning Strategies At Eesp Of Artha Wacana Christian University - Alfred Snae; Yakob Metboki; Nadya Foenale (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
EESP millennial students, based on the result of preliminary study, expecting preferred learning strategies to be applied by the EESP lecturers, especially in pandemic situation. Relating to this, a study conducted to find out the English Education Study Program millennial students’ preferred learning strategies by referring to learning preferences on millennial’s theory suggested by Krishnan (2020). A questionnaire distributed to 120 millennial students of EESP as the participants of this research, and then the descriptive qualitative method applied to analyze the data gotten. The result showed that the strategies mentioned in the theory that are customized content based on individual learning preferences, learn new concepts to practically apply to different scenarios, cross-functional learning with strong feedback loops, preference for non-structured learning environments, and group learning to explore, engage, enquire and achieve as the strategies to teach the millennial students, preferred by the EESP millennial students at Artha Wacana Christian University. Besides, they also prefer more chances to have inquiry-based learning, more activities that engage them in communicative learning, more group discussion, and more audio-visual materials. Therefore, EESP educators and non-EESP educators need to consider and apply those prefer strategies to meet the needs of the millennial students in learning